Deictic Expressions in Nasreddin's Selected Stories - Waladdin Panggabean (Universitas Cokroaminoto Palopo, 2018)
The research discusses deictic expressions or deixis in Nasreddin’s selected stories. The research method applied in the research is qualitative research while the theory that is used in the research is the theory of deixis by Yule that is used to analyze the deictic expressions in the story book. The researcher uses qualitative research because the data of this research are limited to the words or phrases having deictic expressions in the book of Nasreddin, A Man with Thousands Ideas. The aims of this research are to identify the type of deixis and explain the references that appear in the book. The result shows that there are three types of deixis that appear in the book. The analysis also shows that anaphoric and cataphoric references are found in the story book.